The Role of Deep Learning Strategies in Improving Student Activeness in The Islamic Learning Process at State Elementary School 82, Bengkulu City - Prima Wiza Mayoli; Yena Eka Lestari; Wiwinda Wiwinda; Aam Amaliyah (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to describe the role of deep learning strategies in increasing student engagement in the learning process at SD Negeri 82, Bengkulu City. The background of this study is based on the low level of student participation in learning activities, such as asking questions, discussing, and expressing opinions, due to the dominant lecture method still used by teachers. The study used a descriptive qualitative method with data collection techniques in the form of participant observation, in-depth interviews, and documentation. Data analysis was carried out using the Miles & Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results showed that the application of deep learning, which includes the stages of exploration, interpretation, decision-making, and reflection, significantly increased student engagement. Students became more confident in expressing opinions, actively asking questions, and engaging in group discussions. Learning also became more meaningful through project activities, reflection, and the use of trigger questions. Barriers such as differences in students' initial abilities and limited resources can be overcome through scaffolding, the use of simple media, and strengthening the role of teachers as facilitators. This study concludes that the deep learning strategy is effectively implemented at SDN 82 Bengkulu City to foster student engagement and is relevant to the demands of 21st-century learning.